Features and Consequences of Flat Ontology in Expanded Urban Planning. - Wallin, Sirkku; Jarenko, Karoliina; Horelli, Liisa (Taylor & Francis, 2021)
This paper seeks to pinpoint the consequences of the core principles of flat ontology for so-called expanded urban planning, on the basis of four case studies at the local level in the Nordic countries. However, these not only represent the local realms, as they are embedded in glocal networks. Urban development takes place in them through different forms of self-organisation, primarily outside the formal planning processes and official institutions, varying in terms of temporality and stages of emergence. We argue that expanded urban planning, which is based on pluralist realism, opens up methodological opportunities for a more agile and responsive planning system, potentially leading to more inclusive urban development. The comparative analyses indicate that the application of flat ontology comprises an expansion of the extent of planning, the importance of temporal dynamics in all stages of planning, the adoption of a variety of digital and non-digital methods and tools, as well as skillful deliberation of complex relations between assemblages. Thus, flat ontology should be called fat, as it makes the conceptualisation of planning manifold and deliberative instead of linear and hierarchical.
Keywords: Planungstheorie; Planungsbegriff; Stadtplanung; Planungsverständnis; Wohnexperiment; Gemeindeentwicklung; Selbstorganisation; Planungsbeteiligung; Kooperationsmodell; Fallstudie; Vergleichsuntersuchung; Inhaltsanalyse; Informelle Planung; Flache Ontologie